Mechanochemical approach to synthesize citric acid-soluble fertilizer of dittmarite (NH4MgPO4·H2O) from talc/NH4H2PO4 mixture. Issue 30 (6th May 2020) - Tan, Yonghao; Sha, Lin; Yu, Nengkui; Yang, Zhengshuo; Qu, Jun; Xu, Zhigao
Abstract : Dittmarite synthesis by a mechanochemical route for application as a citric acid-soluble fertilizer. Abstract : In this study, a citric acid-soluble fertilizer of dittmarite (NH4 MgPO4 ·H2 O) was synthesized by balling talc with NH4 H2 PO4 . The effects of ball milling speed and milling time on the dissolution rates of N, P and Mg in deionized water and 2% citric acid were explored. Characterization technologies such as X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TG) and Scanning electron microscopy (SEM) were applied to test the prepared samples. In water, the prepared dittmarite was changed into struvite (NH4 MgPO4 ·6H2 O) with almost no N, P or Mg release, while the dissolution rates of nutrient elements reached almost 100% in 2% citric acid. The proposed work presented a facile and environmentally friendly method to produce CASF with high agricultural and ecological value.